1986
DOI: 10.1007/bf02924105
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of nonionic (iopamidol) and ionic (sodium and meglumine diatrizoate) contrast media for urography on urinary excretion of water and solutes

Abstract: Urinary water and solute excretion before and for 40 minutes after intravenous bolus injection of a nonionic (iopamidol) or an ionic medium (sodium meglumine diatrizoate) have been studied in subjects with normal renal function. Iopamidol produced less urinary losses of water, potassium, sodium, and chloride than did diatrizoate; uric acid excretion was also less enhanced. Surprisingly, both contrast agents produced a comparable increase in urinary pH and bicarbonate excretion. These data show that nonionic ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1988
1988
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…The two latter could be explained by osmotic diuresis-induced dilution. Some studies, in agreement with ours, have shown increased UE Na+ 12,31,32 and FE Na+ 32 after ionic and non-ionic radiological contrast, which seems to be independent of contrast osmolality. Increased sodium excretion cannot be explained by sodium content in radiological contrast: diatrizoate has high sodium concentration, while ioxilan, iopamidol, iohexol and other low osmolality contrasts have very low concentrations of this electrolyte.…”
Section: Another Hypothesis To Explain Radiological Contrast Effects supporting
confidence: 91%
“…The two latter could be explained by osmotic diuresis-induced dilution. Some studies, in agreement with ours, have shown increased UE Na+ 12,31,32 and FE Na+ 32 after ionic and non-ionic radiological contrast, which seems to be independent of contrast osmolality. Increased sodium excretion cannot be explained by sodium content in radiological contrast: diatrizoate has high sodium concentration, while ioxilan, iopamidol, iohexol and other low osmolality contrasts have very low concentrations of this electrolyte.…”
Section: Another Hypothesis To Explain Radiological Contrast Effects supporting
confidence: 91%
“…Recently it has been shown that the non-ionic low osmolar IOXILAN, IOHEXOL AND DIATRIZOATE iopamidol increases the excretion of sodium in man, though not to the same extent as diatrizoate (6). Since ioxaglate has also been shown to inhibit the tubular reabsorption of sodium (5), the phenomenon seems independent of contrast medium osmolality and/or charge.…”
Section: Discussionmentioning
confidence: 99%